Relevansi Wawasan Dunia Kristen dan Psikologi Pendidikan dalam Menghadapi Tantangan Pembentukan Karakter Remaja Kristen di Era Digital - Nofanolo Buulolo; Tony Salurante (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2026)
Digital technology has significantly transformed adolescents’ lives, including the process of character formation. While the digital era provides broad opportunities for accessing information and developing personal potential, it also presents challenges such as identity crises, individualism, instant culture, cyberbullying, moral relativism, and declining spiritual engagement. These conditions create unique challenges for Christian adolescents in maintaining values and character grounded in biblical teachings. This study aims to examine the challenges of Christian adolescent character formation in the digital era, analyze the perspectives of the Christian worldview and educational psychology on character development, and explain the relevance of integrating these perspectives in addressing contemporary challenges. The research employed a qualitative approach using a library research method. Data were collected from books, scholarly journals, and other relevant academic sources and analyzed through content analysis. The findings indicate that the Christian worldview provides a theological foundation for shaping identity, values, and character based on biblical truth, while educational psychology offers scientific insights into adolescent development and effective character-building strategies. The integration of these perspectives creates a holistic approach that addresses spiritual, moral, social, emotional, and cognitive dimensions. Therefore, this integration is essential for helping Christian adolescents navigate the challenges of the digital era wisely, responsibly, and in accordance with Christian values.